(untitled) (Al-Academy, 2020)
publishing has become a large space in the field of interactive education and modern pages have become dedicated to the service of the educational effort in this area as the research in this context of the urgent scientific necessities, especially as we consider in Iraq from the new countries in the exploitation of these new technologies and investment possibilities of the information network And the contents of different in the framework of so-called distance education Here lies the problem of research in the possibility of finding scientific solutions for the design of interactive inter active website for students of the preparatory stage in Iraq and to find out the scientific ways to find design The study, which included the problem of research and its importance and objectives and objective, spatial and temporal limits, which were limited in the study of the main pages of educational sites in Iraq and published in 2019, and then came the second chapter Which included the theoretical framework of the study and was on two subjects dealt with to know how to design interactive websites and what their contents and then the most important scientific indicators and then came the third chapter to introduce the procedures and methodology of the study You are according to the descriptive analytical method. The samples were selected by means of two models representing the research community, which consists of the Iraqi educational sites published on the international information network, and then the descriptive analysis was carried out according to a form designed for this purpose after it was modified according to experts’ And the methods of scientific research to give the required results and achieve its goal and scientific goal properly and then came Chapter IV and the last to present the most important findings and recommendations and scientific proposals for research